An IT governance framework for achieving the development of academic programme in higher institutions: A case of Universiti Malaysia Sarawak (UNIMAS) - Nadianatra, Musa; Dayang Hanani, Abang Ibrahim; Noor Alamshah, Bolhassan; Johari, Abdullah; Narayanan, Kulathuramaiyer; Mohamad Nazri, Khairuddin (IEEE, 2015)
In Information Technology (IT) Governance, the use of web has become a competitive strategy for aligning business goals and IT within an organization. IT Governance is a subset of corporate governance. IT Governance is the strategic alignment of IT with business so that maximum business value is achieved through the development and maintenance of effective IT control and accountability, performance management and risk management. As the Internet has connected the organization with people all over the world, providing an effective IT control and achieving risk management over the critical data and services. This is a challenging task to all sectors including education. We modeled a conceptual framework by identifying the elements of governance for achieving the development of academic programme through web based system. For the governance elements, data was collected using qualitative methods. This paper reports on the impact gained from the IT governance framework for the development of academic programme in UNIMAS.